Does mass spectrometric breath analysis detect Pseudomonas aeruginosa in cystic fibrosis?. Issue 3 (4th February 2016) - Pabary, Rishi; Huang, Juzheng; Kumar, Sacheen; Alton, Eric W.F.W.; Bush, Andrew; Hanna, George B.; Davies, Jane C.
Pseudomonas aeruginosa associated with increased morbidity and mortality in cystic fibrosis (CF) can be eradicated if detected early; however, prompt detection is problematic in children and non-expectorating adults as oropharyngeal cultures lack sensitivity [1]. We previously reported that 20% of children with negative oropharyngeal cultures isolated P. aeruginosa on bronchoalveolar lavage [2], but this invasive technique cannot be performed frequently. Hence, there is an urgent need for a noninvasive screening test for lower airways infection in CF; therefore, we propose that exhaled volatile organic compounds (VOC) may be useful biomarkers. Detecting P. aeruginosa infection is problematic; breath analysis shows promise but requires optimisation http://ow.ly/WE1H2